STRUCTURE INTEGRATED PERFORMANCE DEVELOPMENT FOR A COMMERCIAL FRAME - HU Pei; WANG ShuYing; CHEN YouSong; HAN HongYang (Jixie qiangdu)
Finite Element Analysis（ FEA） model of benchmark frame was established and the FEA model was validated by mode and stiffness test; The new develop frame’s mode and stiffness performance was evaluated by this FEA model. For the first torsion mode and the bending stiffness does not meet the requirements of SSTS,optimization design was carried out. Two optimization of increasing cross section and adding new part inside was proposed to improve the frame mode and stiffness performance; ProcessedP latts analysis to select the best optimization and completed the frame structure integrated performance development.